PENGARUH MOTIVASI DAN SEMANGAT KERJA TERHADAP PENINGKATAN PRODUKTIVITAS KERJA KARYAWAN PADA PT. COLOMBUS MEGAH SENTRASARANA DI SAMARINDA - Mukhtar Hidayat (LPPM University 17 Agustus 1945 Samarinda, 2018)
The purpose of this study is to determine the influence of motivation and morale towards the increase of work productivity of employees of PT. Colombus Megah Sentrasarana in Samarinda and to know the improvement of work productivity of employees with the provision of motivation. Analysis uses multiple linear regression with SPSS tool. Correlation coefficient (R) of 0.8770 means that the variables of motivation and morale together have a direct or positive relationship with employee productivity at PT. Colombus Megah Sentrasarana in Samarinda.While the influence of each variable that is variable of motivation (X1) influences work productivity of employee equal to 63,80%, while work spirit variable (X2) influence to work productivity equal to 71,50%. So, it can be said that morale is the dominant variable of influence on employee productivity at PT. Colombus Megah Sentrasarana in Samarinda.The first hypothesis test is acceptable because F count is 69,808 and F table 2,830 which means F arithmetic> F table. The second hypothesis can be accepted because it is proven that the morale of influence dominant effect on employee productivity at PT. Colombus Megah Sentrasarana in Samarinda.